Endophytic bacterium Pseudomonas protegens suppresses mycelial growth of Botryosphaeria dothidea and decreases its pathogenicity to postharvest fruits - Huang, Yonghong; Liu, Junping; Li, Jinghui; Shan, Xiaoying; Duan, Yanxin (Frontiers in Microbiology, 2022)
Apple (Malus domestica Borkh.), one of the most economically important fruits widely consumed worldwide, has been suffering from apple ring rot caused by Botryosphaeria dothidea, which dramatically affects its quality and yield. In the present study, we demonstrated that Pseudomonas protegens isolated from Chinese leek (Allium tuberosum) significantly suppressed the mycelial growth and propagation of Botryosphaeria dothidea, respectively, further displayed a considerably inhibitory effect on the apple ring rot of postharvest fruits. In addition, Pseudomonas protegens significantly improved the total soluble solid/titrable acidity (TSS/TA) ratio and soluble sugar/titrable acidity (SS/TA) ratio and drastically maintained the fruit firmness. Further analysis manifested that Pseudomonas protegens substantially induced the defense-related genes such as MdGLU, MdPAL, MdPOD, MdCAL, and transcription factors related to the resistance to Botryosphaeria dothidea, including MdWRKY15, MdPUB29, MdMyb73, and MdERF11 in apple fruits. Meanwhile, Pseudomonas protegens considerably restrained the expressions of the pathogenicity-related genes in Botryosphaeria dothidea, including the BdCYP450, BdADH, BdGHY, BdATS, Bdα/β-HY, and BdSTR. By inference, Pseudomonas protegens inhibited the apple ring rot on postharvest fruits by activating the defense system of apple fruit and repressing the pathogenic factor of Botryosphaeria dothidea. The study provided a theoretical basis and a potential alternative to manage the apple ring rot on postharvest fruits.